Budget Transparency and Accountability in Local Government - Dian Fathirah; Nirwana, Nirwana; Haliah, Haliah (Asian Journal of Management Analytics, 2024)
This study aims to evaluate the effect of budget transparency and accountability on local government performance, especially in public financial management. This study uses a literature review method by analyzing articles published in the last five years related to the topic of transparency and accountability in the public sector. The results of the study indicate that transparency and accountability play an important role in improving the effectiveness of budget management and the performance of local government employees. Performance-based budgeting has been shown to increase the efficiency of public resource utilization. However, there are challenges in budget absorption, especially at the end of the budget period.